Signal Processing and Analysis of Electrical Circuit - Królczyk, Grzegorz (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue with 35 published articles shows the significance of the topic "Signal Processing and Analysis of Electrical Circuit". This topic has been gaining increasing attention in recent times. The presented articles can be categorized into four different areas: signal processing and analysis methods of electrical circuits; electrical measurement technology; applications of signal processing of electrical equipment; fault diagnosis of electrical circuits. It is a fact that the development of electrical systems, signal processing methods, and circuits has been accelerating. Electronics applications related to electrical circuits and signal processing methods have gained noticeable attention in recent times. The methods of signal processing and electrical circuits are widely used by engineers and scientists all over the world. The constituent papers represent a significant contribution to electronics and present applications that can be used in industry. Further improvements to the presented approaches are required for realizing their full potential.